Logistics Maturity Models: impacts on operational performance and trends for the digital supply chain - Rodrigues, Carlos Manuel Taboada; Gomes, Henrique Costa; Lima, Gislayne de Souza de; Garcia, Mario Vinicio; Zanco, Fernando César (Brazilian Journal of Production Engineering, 2026)
Logistics maturity refers to the level of evolution of an organization’s logistics processes, assessed through models that classify this progression from initial practices to digital and sustainable operations. This study aims to identify and analyze the main logistics maturity models described in recent literature and their impact on organizational performance. A rapid literature review methodology was adopted, suitable for mapping emerging topics efficiently and rigorously. The search, conducted in the Scopus database, prioritized publications from 2022 to 2025 and included relevant Brazilian studies. Sixty-seven articles were initially found, of which thirteen met the inclusion criteria. The results highlight the use of models such as the Capability Maturity Model (CMM), Business Process Orientation (BPO), Digital Maturity Model (DMM), and customized frameworks applied across dimensions like digitalization, sustainability, integration, and operational performance. It is concluded that these models serve as strategic tools for continuous improvement and decision-making support, especially in contexts with different levels of technological development, and that there are opportunities to adapt them to the reality of small and medium-sized Brazilian enterprises.